New local treatment for photoaging using a formulation containing piroxicam 0.8% and sunscreen. Issue 7 (July 2019) - Mazzeo, Mauro; Diluvio, Laura; Di Prete, Monia; Mazzilli, Sara; Garofalo, Virginia; Coniglione, Filadelfo; Orlandi, Augusto; Bianchi, Luca; Campione, Elena
Objective: Skin aging is a complex process influenced by several factors that cause DNA damage and alter the extracellular matrix. The anti-inflammatory drug piroxicam can counteract photocarcinogenesis and photoaging by blocking cyclooxygenases-1 and 2, matrix metalloproteinases, and ornithine decarboxylase, and inducing apoptosis. Methods: We conducted an open observational study in 50 adults with moderate to severe signs of photoaging treated with a new local formulation of piroxicam 0.8% plus sunscreen for 16 weeks. Photoaging was assessed using a validated dermoscopic photoaging scale. Each patient's own perception of their skin quality was assessed using a graphic scale. Results: The new formulation demonstrated a reliable effect on photoaging after 16 weeks, based on improved median dermoscopic photoaging and skin-quality scores. No patients experienced any adverse effects. Conclusions: To the best of our knowledge, this study provides the first evidence for the safe and effective use of a local piroxicam formulation for the treatment of moderate to severe photoaging.